Evaluation of Physical Infrastructure and Seismic Vulnerability in the Community of Joa, Jipijapa Canton - Sornoza Parrales, Diego; Parrales Cantos, Glider Nunilo; Cobos Lucio, Denny Augusto; Villavicencio Cedeño, Erik (Arandu UTIC, 2024)
This research focuses on the evaluation of physical infrastructure and seismic vulnerability in the Joa commune of Canton Jipijapa (Ecuador). The lack of investment in adequate infrastructure can limit the community’s growth and increase its vulnerability to natural disasters. The main objective is to diagnose the infrastructure and evaluate the seismic vulnerability of homes, identifying areas for improvement. The methodology combines surveys of residents and rapid visual assessments of buildings, utilizing the FEMA 154 methodology. The surveys collected information on housing characteristics and residents’ perceptions of structural safety, while the rapid visual assessment classified homes according to their seismic vulnerability. The results showed that most homes are built with reinforced concrete or a combination of concrete and wood. Although most residents perceive little need for rehabilitation, the seismic assessment revealed that a significant percentage of homes have high vulnerability. The zoning map identified the areas of greatest risk. The main conclusion is that there is a worrying number of homes with high vulnerability that require urgent attention. It is recommended to implement reinforcement and rehabilitation programs, as well as education and awareness campaigns about seismic risk. Vulnerability zoning provides essential information for risk management and urban planning, with the aim of reducing the community’s vulnerability to future earthquakes